2020
DOI: 10.5424/sjar/2020183-16146
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining intestinal microflora balance in heat-stressed broilers using dietary creeping wood sorrel (Oxalis corniculata) powder and chromium (chromium picolinate)

Abstract: This study aimed to determine the effect of dietary creeping wood sorrel powder (Oxalis corniculata) and chromium supplemented to broilers (1-42 days) exposed to heat stress, on their performance and on the intestinal and caecal microbiota.Area of study: Ilfov, RomaniaMaterial and methods: The feeding trial was conducted on 60, day-old Cobb 500 broilers, divided equally in two groups, each group with six replicates (5 chicks/ replicate). The broilers were housed in an experimental hall at 32° C constant temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Creeping wood sorrel (CWS) is a well-known medicinal plant with versatile nutritional uses. Regarding the proximate chemical composition, CWS contains a low amount of crude protein and crude fat [6]. Phytochemical composition of CWS showed the presence of niacin, vitamin C and β-carotene, neutral lipids, glyoxylic acid, pyruvic acid, oxalic acid, vitexin and glycolipids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Creeping wood sorrel (CWS) is a well-known medicinal plant with versatile nutritional uses. Regarding the proximate chemical composition, CWS contains a low amount of crude protein and crude fat [6]. Phytochemical composition of CWS showed the presence of niacin, vitamin C and β-carotene, neutral lipids, glyoxylic acid, pyruvic acid, oxalic acid, vitexin and glycolipids [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The chickens had free access to feed and water. Creeping wood sorrel was analyzed, and the data was published previously by Saracila et al [14]. The analysis revealed a concentration of 15.44% CP, 2.83% EE, 4.96 mg/g GAE total polyphenols, 31.60 mmol ascorbic acid equivalent antioxidant capacity and 11.77 mg/100 g vitamin C.…”
Section: Birds Diets and Treatmentsmentioning
confidence: 84%
“…Creeping wood sorrel (Oxalis corniculata) is a little-known plant, which contains an important amount of vitamin C [14] and phenolic compounds with strong free radical scavenging activity [15]. Previous studies demonstrated that including creeping wood sorrel in chicken diet (1%) and Cr picolinate (0.2 mg/kg diet) could counteract the effects of heat stress, resulting in unaffecting growth performance, improving lactobacilli populations and reducing pathogenic bacteria [14].…”
Section: Introductionmentioning
confidence: 99%
“…Global poultry production is affected by environmental stressors causing economic losses due to its influence on health and productive parameters. Since antibiotics have been prohibited in animal nutrition, some additives with antioxidant potential and health enhancers were used as heat stress attenuators like chromium or vitamin C (Saracila et al, 2021, Shehata et al, 2022, natural products like creeping wood sorrel (Saracila et al, 2020), oregano (Vlaicu et al, 2018;Turcu et al, 2018), polyphenols from plants (Hu et al, 2019) and grapeseed or rosehip oils (Vlaicu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%